PEDAGOGICAL PSYCHOLOGICAL OPPORTUNITIES FOR THE DEVELOPMENT OF STUDENT THINKING ACTIVITY IN SCHOOL AND FAMILY COOPERATION - Sherzodbek Ismoilov (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, we aim to ensure that school and family partnerships are organized in a systematic and systematic way to increase the social activity of students, and that they work according to a clear program. The social activity of young people is recommended to understand the objective reality, to express their main social and psychological characteristics, and the generality of their implementation in practice.